Improving The Competence Of Writing And Telling Experiences Through An English Recount Text Using The “Think, Write And Practice” Method In Junior High School Students, Class VIII-2 - Victory Budi Abadi Simbolon; Friska Grace; Theresia Christine Purba; Sondang Manik; Lastri Wahyuni Manurung (Jurnal Pendidikan dan Konseling (JPDK), 2023)
The objective of this research is to improve the Junior High School students in writing and speaking the English recount texts through the Think, Write and Practice method. This classroom action research with three cycles was conducted to the first semester students at VIII-2 of an academic year 2022/2023 in the Bintang Timur Junior High Scholl. The research subjects included 32 students altogether. Data were collected using observation checklist, test, questionnaire, document, and anecdotal record. The obtained data were analyzed descriptively, based on the performance indicator as ? 78 % achievement in writing and speaking recount texts in English. Results show that “The Think, Write and Practice Method” could improve the students’ recount text writing and speaking competency. The process used paper/notes, stationery, experiences list, google translate apps, u-dictionary apps, what’sapp, dictionary books, an active loudspeaker.The performance indicators in writing and speaking recount texts consisted of: choosing clear idea, developing coherent paragraph, structuring sentence, constructing grammatical sentence, and using appropriate diction for writing, and pronunciation, structure, vocabulary, fluency and understanding/contents in speaking. The students’ mean score in writing recount text improved from 67,78 in pre-cycle to 75,01 in cycle 1; 75.51 improved to 78.52. Because there is still one component gets failed, so, it needs the third cycle. In cycle 2 ; and 78,52 improved to 83,11 in cycle 3. Then, it has a significant improvement as well to their speaking competence. In average, pre-cycle it was 66,23. Then it improved to the first cycle. It was 70,79. Next, it reached to 77,33 to the second cycle, till 83,65 in the third cycle. Keywords: Writing, Speaking, Recount Text, Application Abstrak Tujuan dari penelitian ini adalah untuk meningkatkan siswa SMP dalam menulis dan berbicara teks recount bahasa Inggris melalui metode Think, Write and Practice. Penelitian tindakan kelas dengan tiga siklus ini dilakukan pada siswa semester 1 kelas VIII-2 tahun ajaran 2022/2023 di SMP Bintang Timur. Subyek penelitian seluruhnya berjumlah 32 siswa. Pengumpulan data dilakukan dengan menggunakan daftar periksa observasi, tes, angket, dokumen, dan catatan anekdot. Data yang diperoleh dianalisis secara deskriptif, berdasarkan indikator kinerja sebagai ? 78% pencapaian dalam menulis dan berbicara teks recount dalam bahasa Inggris. Hasil penelitian menunjukkan bahwa “Metode Berpikir, Menulis, dan Berlatih” dapat meningkatkan kompetensi menulis dan berbicara teks recount siswa. Prosesnya menggunakan kertas/catatan, alat tulis, daftar pengalaman, aplikasi google translate, aplikasi kamus, what'sapp, buku kamus, pengeras suara aktif. Indikator kinerja dalam menulis dan berbicara teks recount terdiri dari: memilih ide yang jelas, mengembangkan koheren paragraf, menyusun kalimat, menyusun tata bahasa kalimat, dan menggunakan diksi yang tepat untuk menulis, dan pengucapan, struktur, kosa kata, kelancaran dan pemahaman / isi dalam berbicara. Nilai rata-rata siswa dalam menulis teks recount meningkat dari 67,78 pada pra-siklus menjadi 75,01 pada siklus 1; 75,51 membaik menjadi 78,52. Karena masih ada satu komponen yang gagal, maka diperlukan siklus ketiga. Pada siklus 2 ; dan 78,52 meningkat menjadi 83,11 pada siklus 3. Kemudian, ada peningkatan yang signifikan juga pada kompetensi berbicara mereka. Rata-rata pra siklus adalah 66,23. Kemudian ditingkatkan ke siklus pertama. Itu 70,79. Selanjutnya mencapai 77,33 pada siklus kedua, menjadi 83,65 pada siklus ketiga. Kata Kunci: Menulis, Berbicara, Teks Recount, Aplikasi